PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN DI TARKOPI CAFE PANYABUNGAN KABUPATEN MANDAILING NATAL - Indah Aminah Putri; Lilia Afriani; Rosnani Siregar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The market is an activity that forms the price of an item that occurs through a certain mechanism. The market plays an important role in improving the economy of a country. Price greatly influences profit or profit in a business. The higher the price, the lower the purchasing decision and the lower the profit, conversely, if the price is low the purchasing decision becomes higher and the more profit you get at Tarkopi Cafe Panyabungan II, Mandailing Natal Regency. After conducting research on prices and profits at Tarkopi Cafe Panyabungan II, Mandailing Natal Regency, the partial test (t) was obtained at 26.789 and the ttable value was 1.661. So the tcount value is greater than ttable, namely 26.789, greater than 1.661 (26.789 > 1.661) which shows that the price variable (X) has a positive and significant impact on profit (Y) with an R Square value of 0.884 times 100% = 88.4% and the remaining 11.6% is influenced by other variables.